Unveiling Microbiota Profiles in Saliva and Pancreatic Tissues of Patients with Pancreatic Cancer - Alper Uguz; Can Muftuoglu; Ufuk Mert; Tufan Gumus; Deniz Ece; Milad Asadi; Ozlem Ulusan Bagci; Ayse Caner (Microorganisms)
The pancreas, previously considered a sterile organ, has recently been shown to harbor its own microbiota that may influence tumor biology and patient outcomes. Despite increasing interest in the impact of the microbiome on cancer, the relationship between pancreatic tissue and oral microbiomes in pancreatic ductal adenocarcinoma (PDAC) remains limited. In this study, the oral and pancreas tissue microbiomes of patients with PDAC were compared to patients with other periampullary cancers (DC/AC) and a healthy control group using 16S rRNA gene sequence analysis. The results showed a significant reduction in microbial diversity in the saliva of cancer patients compared to healthy controls, while the PDAC patients exhibited a distinct microbial profile in their pancreatic tissues, consisting predominantly of Firmicutes, Proteobacteria, and Actinobacter, after filtering the microbiome of the indoor environment. Notably, the presence of oral bacteria such as Anoxybacillus, Clostridium, and Bacillus in pancreatic tissues suggests potential translocation from the oral cavity. This study emphasizes the importance of understanding the role of body fluid and tissue microbiota in pancreatic cancer, proposing that oral dysbiosis may contribute to disease progression. Moreover, the results suggest that the microbiome of the indoor environment in which samples are collected and analyzed is also important in microbiota analysis studies.